Laboratory evaluation of fiber-modified asphalt mixtures incorporating steel slag aggregates - Alnadish A.M.; Aman M.Y.; Katman H.Y.B.; Ibrahim M.R. (Tech Science Press, 2023)
Asphalt mixtures; Cracks; Electric arcs; Electric furnaces; Mixtures; Polyesters; Polyvinyl alcohols; Reinforced plastics; Reinforcement; Slags; Steel fibers; Sustainable development; Synthetic fibers; Acrylic fibers; Cracking resistance; Modified asphalts; Performance; Polyester fibre; Polyvinyl alcohol fiber; Reinforced asphalt mixtures; Resilient modulus; Steel slag; Steel slag aggregate; Aggregates